Interspecific plant functional variation prevails over intraspecific variation in driving spider beta diversity - Gusmao, Paulo H. P.; Sena, Pedro H. A.; Bernabe, Tiago N. [UNESP]; Ouchi-Melo, Lilian S. [UNESP]; Goncalves-Souza, Thiago (Wiley-Blackwell, 2019)
1. Non-trophic interactions between plants and animals can affect community structure and species trait composition. However, it is unclear how changes in intra- and interspecific morphological traits of plant species affect non-trophic interactions at a metacommunity scale. Additionally, whether plant evolutionary history determines taxonomic and functional diversity of plant-dwelling predators is an open question. 2. To address these gaps, this study used a published dataset with spiders dwelling exclusively on bromeliads to investigate if: (i) intra- and interspecific variability in host plant morphological traits affects spider taxonomic and functional diversity; and (ii) bromeliad trait evolution determines present-day patterns of spider trait diversity. 3. Spider and bromeliad traits were measured, and a new statistical framework was used to quantify the response of spider beta diversity to intra- and interspecific variation in bromeliad traits. In addition, bromeliad traits were decomposed across its phylogenetic tree to check whether the current variation in morphological traits of bromeliads is a result of either ancestral or recent diversification. 4. Bromeliad intraspecific variation did not affect spiders, but leaf length variation between bromeliad species had a positive effect on spider functional beta diversity. Interestingly, the most ancestral split between two subfamilies explained most of the variation in bromeliad species, which suggests that spider functional diversity could represent an outcome of bromeliad evolutionary history. 5. Overall, the results of this study suggest that interactions between plants and organisms that do not feed directly on their tissues could be shaped by plant evolutionary history, which in turn suggests that non-trophic interactions can be maintained over time.
Keywords: Arthropods; biotic filter; bromeliads; evolutionary history; non-trophic interactions